2014
DOI: 10.2478/pjct-2014-0003
|View full text |Cite
|
Sign up to set email alerts
|

Selective recovery of cobalt(II) towards lithium(I) from chloride media by transport across polymer inclusion membrane with triisooctylamine

Abstract: In this work the selective transport of cobalt(II) and lithium(I) ions from aqueous chloride solutions through polymer inclusion membranes (PIMs) is presented. Triisooctylamine (TIOA) has been applied as the ion carrier in membrane. The effects of various parameters on the transport of Co(II) and Li(I) were studied. The obtained results show that Co(II) ions were effectively removed from source phase through PIM containing 32 wt.% TIOA, 22 wt.% CTA (cellulose triacetate) and 46 wt.% ONPOE (o-nitrophenyl octyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Recently, ionic liquids (ILs) have been used as extractants or ion carriers for metal ions from aqueous solutions. ILs exhibit many unique properties, such as: negligible vapor pressure, high thermal stability, non-flammability and good extractability for various organic compounds as well as for metal ions [ 23 , 24 ]. Room temperature ionic liquids (RTILs) are an alternative to replace organic solvents because they are able to dissolve both polar and non-polar compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ionic liquids (ILs) have been used as extractants or ion carriers for metal ions from aqueous solutions. ILs exhibit many unique properties, such as: negligible vapor pressure, high thermal stability, non-flammability and good extractability for various organic compounds as well as for metal ions [ 23 , 24 ]. Room temperature ionic liquids (RTILs) are an alternative to replace organic solvents because they are able to dissolve both polar and non-polar compounds.…”
Section: Introductionmentioning
confidence: 99%
“…• acidic carriers-capable of exchanging a proton for a metal ion; the most commonly used transporters of this group include organophosphorus acids (e.g., D2EHPA, Cyanex 272, Cyanex 303) [25,[36][37][38], as well as hydroxyoximes (e.g., LIX-84 I) [39][40][41]; • alkaline carriers-organic compounds whose nature corresponds to Lewis bases; they form ionic pairs with metal ions. This group includes quaternary ammonium [42][43][44] and phosphonium salts [33,43], tertiary amines [44,45], pyridine and pyridine derivatives [6,46,47], and alkyl imidazole derivatives [8,27,48]; • inert carriers-capable of forming an inert complex with metal ions in the organic phase by replacing the water molecules in the metal aqua complex with their own molecules, which are more lyophilic. The group of these transporters includes such compounds as phosphoric acid esters [49,50] and phosphinic acid esters [51].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous metal extraction, transport, and separation studies involving the use of PIMs containing extractants as metal carriers have been reported . Some Co(II) extraction and/or transport studies using PIMs have also been reported and they include the separation of Co(II) from Ni(II) and Li(I) . However, to the best of our knowledge the separation of Co(II) from Mn(II) using PIMs has never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, the inclusion of a modifier to increase the solubility of the extracted species in the membrane liquid phase may be required. In solid‐phase extraction using PIMs, metal ions are generally extracted by mechanisms similar to those in conventional solvent extraction processes . These mechanisms are often based on the formation of complexes and ion‐pairs with the extractant at the membrane/feed solution interface …”
Section: Introductionmentioning
confidence: 99%